Pelatihan Teknik Dasar Penulisan Artikel Ilmiah bagi Guru SMK - Nurdin, Erdawati; Fitraini, Depi; Nufus, Hayatun; Hasanuddin, Hasanuddin (Catimore: Jurnal Pengabdian Kepada Masyarakat, 2025)
The implementation of this community service activity was carried out in response to the limited knowledge of teachers regarding scientific writing, even though scientific writing is a strategic component in supporting the professional development of teachers. Therefore, this activity aims to equip mathematics subject teacher forum (MGMP) teachers at vocational high schools (SMK) in Indragiri Hilir Regency with an understanding of the basic principles of scientific article writing, technical skills, and strategies for publishing scientific articles based on the result of classroom action research (PTK).